2023
DOI: 10.21037/gs-22-589
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green fluorescence guided resection of parathyroid adenoma of the carotid sheath: a case report and review of the literature

Abstract: Background: Ectopic parathyroid tissue can pose difficulties in diagnosis, management, and resection of adenomas in patients with hyperparathyroidism. The use of multimodal pre-operative imaging is recommended due to the diverse anatomic presentation of parathyroid adenomas and the potential presence of multiple adenomas. Resection failure still can occur, however, indocyanine green (ICG) fluorescence imaging is an intraoperative tool that has potential to help address this challenge. In the case which follows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Dissection of the common bile duct could lead to collateral damage and hemorrhage. 31 ICG-FI enables the surgeon to visualize the shape of the extrahepatic bile ducts, [32][33][34] in combination with 3DVT to accurately locate crucial vascular structures, 35 thereby reducing surgical iatrogenic injuries. The surgical treatment of diffuse hepatolithiasis is challenging, as hepatectomy combined with choledochotomy fails to completely remove all stones in the distal intrahepatic bile ducts.…”
Section: Discussionmentioning
confidence: 99%
“…Dissection of the common bile duct could lead to collateral damage and hemorrhage. 31 ICG-FI enables the surgeon to visualize the shape of the extrahepatic bile ducts, [32][33][34] in combination with 3DVT to accurately locate crucial vascular structures, 35 thereby reducing surgical iatrogenic injuries. The surgical treatment of diffuse hepatolithiasis is challenging, as hepatectomy combined with choledochotomy fails to completely remove all stones in the distal intrahepatic bile ducts.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,14 In head and neck surgeries, ICG was initially used to help preserve the parathyroid glands during thyroidectomy with a dose of 25 mg of ICG powder in 10 ml of sterile water administered intravenously in a dose of 3 ml, which can be repeated up to a maximum of 5 mg/ kg. [15][16][17] In a study comparing 2 scoring systems (ICG-2 vs. ICG-4), in which they used the classification used to measure the vascularity of the glands, which divides the color of the glands as: black for not vascularized (Score 0), gray as partially vascularized (Score 1) and white, as a well vascularized (Score 2). The ICG-4 system based on the sum of the score value of the 4 glands translates to a score of 2 in at least one gland of the ICG-2 has a higher diagnostic accuracy than that obtained from the sum of the score of each gland and for the cut point ≤3 of ICG-4.…”
Section: Discussionmentioning
confidence: 99%
“…17 Zaidi et al demonstrated the usefulness of fluorescence imaging, specifically for patients undergoing initial surgery for primary hyperparathyroidism, showing that 92.9% of the glands visible to the naked eye demonstrated ICG uptake and that all 33 patients in the study were biochemically cured of their hyperparathyroidism after surgery. 15,16 In another study involving 60 patients, 54 patients underwent preoperative sestamibi scintigraphy, of which 36 patients were identified as having a parathyroid adenoma, while 18 patients had no abnormalities. However, of these 18 patients, a fluorescent adenoma on indocyanine green imaging was found.…”
Section: Discussionmentioning
confidence: 99%
“…In the manuscript of Gland Surgery , Rupp et al shed light on this topic. They present the case of a 75-year-old woman diagnosed with PHPT due to a parathyroid adenoma localized to the left carotid sheath ( 6 ). Localization of an ectopic inferior parathyroid gland adenoma within the left posterior carotid sheath of the patient was confirmed using single photon emission computed tomography/computed tomography (SPECT/CT) and ultrasound.…”
mentioning
confidence: 99%